Climate Smart Bread Wheat (Triticum aestivum L.) Variety Development for Optimum Moisture Areas of Ethiopia - Alemu, Gadisa; Dabi, Alemu; Sime, Berhanu; Geleta, Negash; Delesa, Abebe; Zegaye, Habtemariam; Duga, Ruth; Kasahun, Cherinet; Negash, Tamirat; Solomon, Tafesse; et al. (International Journal of Bio-resource and Stress Management, 2023)
A study was undertaken during the 2017–18 to 2018–19 cropping seasons at at eleven locations and/or seventeen environments in optimum moisture areas of Ethiopian to identify stable genotypes with high grain yield and release as a variety for optimum-moisture environments. Alpha-lattice design with three replications was used. The combined ANOVA revealed very highly significant differences (p≤0.001) among genotypes, environments, and GEI for yield and its components. The environment sum of squares contributed more than the genotype and GEI sum of squares for the total variance of all traits. When we consider the overall mean for grain yield, genotype ETBW8751 (5.12 t ha-1) the highest value followed by ETBW9554 (5.10 t ha-1) whereas the lowest grain yield was obtained from the genotype ETBW8804 (3.67 t ha-1). GGE and AMMI analysis explained almost similar amounts of variation; however, AMMI still show a slightly greater proportion than GGE during our study. According to AMMI and GGE analysis genotype 21 (ETBW9553) was more stable as well as high yielding followed by 22 (ETBW9554) and 2 (ETBW8751. Conversely, 15 (ETBW9547) was unstable, but high yielding. Hidasse had low yields but was unstable. ETBW9554 was validated on farmers’ fields and recommended for registration as a commercial variety and finally released in 2020 with its designated local name “Boru” for commercial production for mid to highland agro-ecologies in Ethiopia.